MATHEMATICAL MODELS FOR MAKING THE COMPUTERIZED SYSTEMS OF ECOLOGICAL MONITORING - Sobirjonova, G.Q. (Educational Research in Universal Sciences, 2023)
Nowadays ecological problems have become actual. Active assimilation of nature and fast-going development of production of technologies led to growth in welfare of human being, but at the same time assisted to ecological crisis extension. In order to solve the appearance of problems, the balance between ecological safety and economical impact of agricultural complex should be held.